Answer:
![4\sqrt{10}](https://tex.z-dn.net/?f=4%5Csqrt%7B10%7D)
Step-by-step explanation:
![\sqrt{160}](https://tex.z-dn.net/?f=%5Csqrt%7B160%7D)
![\sqrt{16 * 10}](https://tex.z-dn.net/?f=%5Csqrt%7B16%20%2A%2010%7D)
![4\sqrt{10}](https://tex.z-dn.net/?f=4%5Csqrt%7B10%7D)
because 16 is a perfect square root and it splits into 4 * 4 while 10 isnt a perfect square root so it stays inside.
Answer:
![f^{-1}(x) = log_{12}(y)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20log_%7B12%7D%28y%29)
Step-by-step explanation:
We have the following function
y = 12^x, and we need to find the inverse function.
To find the inverse function we should solve the equation for "x". To do so, first, we need to:
1. Take the logarithm in both sides of the equation:
lg_12 (y) = log _12 (12^x)
(Please read lg_12 as: "Logarithm with base 12")
From property of logarithm, we know that lg (a^b) = b*log(a)
Then:
lg_12 (y) = x*log _12 (12)
We also know that log _12 (12) = 1
Then:
x = log_12(y).
Then, the inverse of: y= 12^x is:
![f^{-1}(x) = log_{12}(y)](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28x%29%20%3D%20log_%7B12%7D%28y%29)
Answer:
h(-5) = 34
Step-by-step explanation:
h(x) = -5x + 9
h(-5) = -5(-5) + 9 = 25 + 9 = 34
Answer: a) No Solution
b) Infinite Solutions (All Real Numbers)
<u>Step-by-step explanation:</u>
4(g + 8) = 7 + 4g
4g + 32 = 7 + 4g <em>distributed 4 into g + 8</em>
32 = 7 <em> subtracted 4g from both sides</em>
Since the statement is false because 32 ≠ 7, then there is NO SOLUTION
-4(-5h - 4) = 2(10h + 8)
20h + 16 = 20h + 16 <em>distributed</em>
16 = 16 <em>subtracted 20h from both sides</em>
Since the statement is true because 16 = 16, then there are INFINITE SOLUTIONS so x can be all real numbers.
Answer:
See verification below
Step-by-step explanation:
We can differentiate P(t) respect to t with usual rules (quotient, exponential, and sum) and rearrange the result. First, note that
![1-P=1-\frac{ce^t}{1+ce^t}=\frac{1+ce^t-ce^t}{1+ce^t}=\frac{1}{1+ce^t}](https://tex.z-dn.net/?f=1-P%3D1-%5Cfrac%7Bce%5Et%7D%7B1%2Bce%5Et%7D%3D%5Cfrac%7B1%2Bce%5Et-ce%5Et%7D%7B1%2Bce%5Et%7D%3D%5Cfrac%7B1%7D%7B1%2Bce%5Et%7D)
Now, differentiate to obtain
![\frac{dP}{dt}=(\frac{ce^t}{1+ce^t})'=\frac{(ce^t)'(1+ce^t)-(ce^t)(1+ce^t)'}{(1+ce^t)^2}](https://tex.z-dn.net/?f=%5Cfrac%7BdP%7D%7Bdt%7D%3D%28%5Cfrac%7Bce%5Et%7D%7B1%2Bce%5Et%7D%29%27%3D%5Cfrac%7B%28ce%5Et%29%27%281%2Bce%5Et%29-%28ce%5Et%29%281%2Bce%5Et%29%27%7D%7B%281%2Bce%5Et%29%5E2%7D)
![=\frac{(ce^t)(1+ce^t)-(ce^t)(ce^t)}{(1+ce^t)^2}=\frac{ce^t+ce^{2t}-ce^{2t}}{(1+ce^t)^2}=\frac{ce^t}{(1+ce^t)^2}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B%28ce%5Et%29%281%2Bce%5Et%29-%28ce%5Et%29%28ce%5Et%29%7D%7B%281%2Bce%5Et%29%5E2%7D%3D%5Cfrac%7Bce%5Et%2Bce%5E%7B2t%7D-ce%5E%7B2t%7D%7D%7B%281%2Bce%5Et%29%5E2%7D%3D%5Cfrac%7Bce%5Et%7D%7B%281%2Bce%5Et%29%5E2%7D)
To obtain the required form, extract a factor in both the numerator and denominator:
![\frac{dP}{dt}=\frac{ce^t}{1+ce^t}\frac{1}{1+ce^t}=P(1-P)](https://tex.z-dn.net/?f=%5Cfrac%7BdP%7D%7Bdt%7D%3D%5Cfrac%7Bce%5Et%7D%7B1%2Bce%5Et%7D%5Cfrac%7B1%7D%7B1%2Bce%5Et%7D%3DP%281-P%29)